New neurons in the adult striatum: from rodents to humans. Issue 9 (September 2015) - Inta, Dragos; Cameron, Heather A.; Gass, Peter
Highlights: Recently, adult neurogenesis was shown to occur in the normal human striatum. Similar newborn-specific striatal interneurons were described in different species. Adult-generated striatal neurons may derive from the pallium/subventricular zone. Adult striatal neurogenesis could be of relevance for neuropsychiatric disorders. Abstract : Most neurons are generated during development and are not replaced during adulthood, even if they are lost to injury or disease. However, it is firmly established that new neurons are generated in the dentate gyrus of the hippocampus of almost all adult mammals, including humans. Nevertheless, many questions remain regarding adult neurogenesis in other brain regions and particularly in humans, where standard birth-dating methods are not generally feasible. Exciting recent evidence indicates that calretinin-expressing interneurons are added to the adult human striatum at a substantial rate. The role of new neurons is unknown, but studies in rodents will be able to further elucidate their identity and origin and then we may begin to understand their regulation and function.